From bullied to brilliant : how to artfully avoid fitting in - Clarke, Karen; Gandhi, Arun ([Yandina, Queensland] : Karen Clarke, 2015)
From Bullied to Brilliant' is a refreshingly and rather unconventional way of problem solving in a world where bullying is commonplace and resources are few and far between. Discover how to rapidly end the cycle of bullying, dominance and intimidation and find your inner brilliance. Are you a victim of bullying, or the parent of a victim? A surprisingly large percentage of our society have experienced intimidation, aggression and bullying. Many have fallen into the unpleasant, unnecessary and slippery trap of believing the bully and are now feeling unworthy or low in confidence and self-esteem. Bullies themselves often don't understand why they behave the way they do, and interestingly the feelings they experience, of social discomfort and a lack of confidence, are much the same as their victims. Through a series of contributed case studies and also some of our own stories, we experience real life examples of bullying, intimidation or threat, and work to unravel the meaning behind it all.
Foreword by Dr. Arun Gandhi.
Includes bibliographical references (pages 253-254)
Keywords: Bullying; Bullying -- Prevention; Victims of bullying; Aggressiveness in children; Children -- Life skills guides; Aggressiveness in children; Bullying; Bullying -- Prevention; Children; Australian; Life skills guides